Model-Driven Constraint Engineering - Wahler, Michael; Koehler, Jana; Brucker, Achim (Electronic Communications of the EASST, 2007)
Precise specification of meta-models is an important rerequisite for the successful application of a model-driven engineering (MDE) process. One means of precise specification are textual constraints. However, the task of constraint development is time-consuming and error-prone if done manually. In this paper, we present both a methodology and a tool for developing constraints in a systematic way that can be integrated into a CASE tool. Thus, we provide a semi-automated means for integrating constraints into the MDE process. Our approach is based on an extensible library of generic constraint patterns. Constraint patterns can be combined to create complex constraints and easily parameterized in a CASE tool. Moreover, we show how these parameterized patterns are transformed into platform-independent or platform- specific constraints by a model transformation.